Performance Appraisal Design In The Grand Mutiara Hotel Housekeeping Division Using BARS Assessment Model - Muhammad Fachrurrozi Akbar (International Journal of Innovation in Enterprise System, 2021)
Frequently receiving customers complaints makes the Grand Mutiara Hotel decrease in monthly guests number, caused by customer’s dissatisfaction with the hotel’s facilities and services. It occurs due to the crew’s disappointment, especially in the housekeeping division dealing with their working-performance assessment to be an indicator of salary payment. Redesigning the assessment was carried out by paying attention to factors affecting the working performances. The subject of this research was the Grand Mutiara Hotel. This research utilized the BARS (Behavior Anchor Rating Scale) method that was an effort to diagnose and reveal individual behavior to be suitable with the company’s objectives. This method aimed to determine which factors influencing the working-performance and delivering the assessing guideline containing clear indicators should be in those factors. Sampling used a purposive random sampling by taking two respondents in each sub-group consisting of housekeeping, security, F&B, engineering, and front office divisions. Further, other samples were coming from supervisors of each sub-group, managers, and HRD. This study indicates five factors affecting the working-performance, such as tangibility, reliability, assurance, responsiveness, and empathy.